Tropical South American Rainfall Response to Dansgaard-Oeschger Stadials of Marine Isotope Stage 5 - Venancio, Igor M.; Nascimento, Rodrigo A.; Santos, Thiago P.; Belem, Andre L.; Lessa, Douglas O.; Tiedemann, Ralf; Chiessi, Cristiano M.; Mulitza, Stefan; Albuquerque, Ana Luiza S. (Frontiers in Earth Science, 2022)
Tropical precipitation patterns will most likely be altered by future climate change, with major socioeconomic consequences for human populations that are highly reliant on water availability for subsistence like populations in northeastern (NE) Brazil. Socioeconomic consequences may be particularly disruptive in the occurrence of abrupt climate change. Understanding the response of tropical precipitation to abrupt climate change is a crucial task for improving future projections and devising adaptation policies. Past abrupt climate change events such as the Dansgaard-Oeschger (DO) cycles may provide relevant insights regarding the dynamics of the climate system under this type of climate change. Here we present a paleoceanographic reconstruction off NE Brazil based on geochemical analyses (stable oxygen isotopes, Mg/Ca and Ba/Ca) performed in planktonic foraminifera, that focus on DO stadials of Marine Isotope Stage 5 (MIS5). Our new Ba/Ca record shows increases in fluvial discharge linked to enhanced continental precipitation over NE Brazil during DO stadials of MIS5. Tropical precipitation patterns were altered with enhanced rainfall in NE Brazil during DO stadials as a consequence of a southward displacement of the Intertropical Convergence Zone, which, in turn, was likely a response to changes in ocean heat transport and sea ice cover, as highlighted by recent climate model simulations. The results presented here provide useful information on how abrupt climate change can impact tropical rainfall, which is crucial for tropical societies in order to delineate strategies to cope with future climate change.